Evaluation of foodborne disease outbreaks proved by laboratory test in the city of Campinas, SP - between 1987 and 1993. - Predominance of outbreaks in food service establishments and etiologic agents involved - Helena C.R. Passos, Maria (1996)
Between 1987 and 1993, the local Health Protection Department investigated 53 foodborne disease outbreaks in the city of Campinas, State of São Paulo, Brazil. Nineteen outbreaks were confirmed through laboraty testing. Foods prepared in foodservice establishments accounted for 14(73,6%) of the outbreaks, while foods mishandled in homes and in bakeries/confectioneries accounted for 3(15,8%) and 2(10,5%), respectively. The results indicated that Bacillus cereus and Staphylococcus aureus were accountable, respectively, for 68,4 and 31,6% of the total outbreaks. Bacillus cereus accounted for 78,6% and S. aureus for 21,4% of the outbreaks associated with foodservice establishments. This paper discusses the importance of these microorganisms as etiologic agents of foodborne disease outbreaks and the main factors which contributed to the occurrence of these incidents.